Spectrophotometric determination of polyphenols in green teas with 18-molybdodiphosphate - Al-Shwaiyat, Mohammed; Denisenko, Tatyana; Miekh, Yuliia; Vishnikin, Andriy (Lviv Politechnic Publishing House, 2018)
Оцінено реакційну здатність 18-молібдоди- фосфатного гетерополікомплексу (18-МФК) щодо поліфеноль- них сполук, які містяться в зелених чаях. В таких реакціях в залежності від співвідношення відновника до 18-MФК спів- існують одно- та двоелектронні гетерополісині. Результати визначення загального вмісту поліфенолів у зелених чаях різних марок, отриманих з 18-МФК та реагентом Фоліна-Чокальтеу, близькі один до одного. Показані недоліки існуючих методів.

The reactivity of 18-molybdodiphosphate heteropoly complex (18-MPC) with respect to the polyphenolic compounds contained in green teas was estimated. The one- and two-electron heteropoly blues coexist depending on the ratio of reducing agent to 18-MPC in such reactions. The results for the determination of total content of polyphenols in green teas of different brands obtained with 18-MPC and Folin- Ciocalteu reagent are close to each other. The disadvantages of the existing methods are shown.
Спектрофотометричне визначення поліфенолів в зелених чаях з 18-молібдодифосфатом
Keywords: спектрофотометрія; гетеропо- лікомплекси структури Доусона; реактив Фоліна-Чокальтеу; 18-молібдодифосфат; катехіни; spectrophotometry; Dawson heteropoly complexes; Folin-Chiocalteu reagent; 18-molybdodiphosphate; catechins; tea analysis